Great book of grilled cheese : 100+ recipes for the ultimate comfort food, soups, salads, and sides - Wilcox, Kim (Chef) (Fox Chapel Publishing, 2021)
"Cheese toastie, Welsh rarebit, croque monsieur--whatever you call it, everyone loves a warm and crispy grilled cheese sandwich! A must-have cookbook filled with more than 100 recipes for grilled cheese sandwiches, soups, sides, and even desserts, Great Book of Grilled Cheese is sure to be a crowd-pleaser for the whole family! With classic, specialty, and regional grilled cheeses and sides--including vegetarian options--this ultimate guide to grilled cheese offers endless, out-of-the-box possibilities for everyone's favorite comfort food, plus what to serve with it, so you'll never run out of cooking ideas or inspiration again! Using easy ingredients, you'll discover amazing options for delicious grilled cheese sandwiches, plus the perfect side pairings--from deviled bacon grilled cheese to creamy tomato basil soup and from a Cinco de Mayo grilled cheese to buffalo tater tots. Included with each recipe is a charming introduction that provides context and captures chefs' kitchen memories"--Amazon.com